The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1051/matecconf/201714902065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quick lime on physicochemical properties of clay soil

Abstract: Abstract. Clay soils are known for their water sensitivity, which causes irreparable damage to any structure built on this type of soil. In order to avoid such problem, it is necessary to use various improvement and stabilization methods such as treatment with lime. This process has been used successfully in the field for decades. The addition of lime generates various physicochemical reactions within the soil such as cation exchange and pozzolanic reactions which are largely responsible for the improvement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The surface morphology tends to be having higher roughness after the addition of hydroxyapatite as seen in the top row of Figure 5A. The presence of Ca 2+ from hydroxyapatite results in the clay particles agglomeration to become larger aggregates 30–32 . This phenomenon can be explained as follows: the positive charge of Ca 2+ diffuses to insert between the negative charges of clay particles causing decrease of the repulsive electrostatic force between the clay particles.…”
Section: Resultsmentioning
confidence: 97%
“…The surface morphology tends to be having higher roughness after the addition of hydroxyapatite as seen in the top row of Figure 5A. The presence of Ca 2+ from hydroxyapatite results in the clay particles agglomeration to become larger aggregates 30–32 . This phenomenon can be explained as follows: the positive charge of Ca 2+ diffuses to insert between the negative charges of clay particles causing decrease of the repulsive electrostatic force between the clay particles.…”
Section: Resultsmentioning
confidence: 97%
“…Lime is used to stabilize a variety of materials including weakly alkaline soils, turning them into "workbenches" or subbases; and with a marginal granular base material, namely gravel-clay, "dirty" gravel, to form a strong and high-quality base layer (Guyer, 2011). Several studies on the mechanism of the basic lime-clay reaction have been reported in the literature (Balaji et al, 2018;Beetham et al, 2015;Bessaim et al, 2018;Devi et al, 2018) Efforts to improve and stabilize soil properties can be carried out with various techniques, including addition of lime (Ali & Mohamed, 2017;Bell, 1996;Garzón et al, 2016). One of the commonly used techniques is the remediation method, because of its facilities and economic appearance, on the other hand, because of its effectiveness in obtaining engineering materials that have superior properties.…”
Section: Introductionmentioning
confidence: 99%
“…Limited by regional soil conditions, many studies focus on expansive soils and clays. However, the application of lime-solidified loess is also extensive, and some studies mainly highlight the mechanical and physical properties of solidified soil [6,[19][20][21]. However, loess has restricted regional characteristics and is quite different from expansive soil in terms of engineering characteristics.…”
Section: Introductionmentioning
confidence: 99%